(untitled) (Research, Society and Development, 2020)
Population development provides an increase in demand for water resources, but some surface water sources do not meet the demanded flow or present qualitatively unsatisfactory conditions for consumption. In this way, the use of underground springs is increasing, mainly for public supply, however the uncontrolled extraction of natural resources becomes a threat to the supply of municipal water. The work analyzed the behavior of the potentiometric level of the Bauru Aquifer, in the central area of ​​the Municipality of São José do Rio Preto, through information from 298 wells, collected in two databases, in the DAEE (Department of Water and Electricity) of Araraquara and SIAGAS (Groundwater Information System). Correlations between variables were performed and, through analysis of variance, the difference between periods was detected, and regressions were performed to show the behavior of the data set over time. The maps of the potentiometric level of the spring were built in the Surfer software by applying the ordinary kriging technique. The results demonstrate a decrease of 10 m in the potentiometric level of the aquifer, which occurred in the 2000s, which in the long run should compromise the potential of the source, requiring the implementation of management techniques to avoid depletion of the source in the central region of the municipality.